Survival analysis of PLWHA undergoing combined antiretroviral therapy: exploring long-term prognosis and influencing factors - Pu, Jun-fan; Wu, Jing (Frontiers in Public Health, 2024)
The survival time of human immunodeficiency virus (HIV)-infected individuals or patients with acquired immunodeficiency syndrome (AIDS) is influenced by multiple factors.Studying survival and influential factors after antiretroviral therapy (ART) contributes to improving treatment protocols, management strategies, and prognosis for people living with HIV/AIDS (PLWHA).Methods: This retrospective cohort study collected case data and follow-up records of HIV/AIDS patients who received ART in Dazu District, Chongqing City, between 2007 and 2022. Cumulative survival rates were calculated using life tables. Survival curves were plotted using the Kaplan-Meier method. Uni-variable and multivariable Cox proportional hazards models analyzed factors influencing survival.The study included 5,237 PLWHA receiving ART. Within the first year of ART initiation, 149 AIDS-related deaths occurred, accounting for 30.10% (149/495) of total deaths. Cumulative survival rates at 1, 5, 10, and 15 years were 0.97, 0.90, 0.85, and 0.79, respectively. During the observation period, male patients who received ART had a 1.89 times higher risk of death compared to females (aHR, 1.89; 95%; CI, 1.50-2.37). Patients aged ≥60 years had a 3.44-fold higher risk of death than those aged <30 years (aHR, 3.44; 95% CI, 1.22-9.67). Injection drug users (aHR, 4.95; 95% CI, 2.00-12.24) had a higher risk of death than those with heterosexual (aHR, 1.60; 95% CI, 0.69-3.72) and homosexual transmission. Patients with a baseline CD4+ T lymphocyte count <200 cells/μL (aHR, 8.02; 95% CI,) and between 200 and 349 cells/μL (aHR, 2.14; 95% CI, 1.26-3.64) had a higher risk of death than those with ≥350 cells/μL. Patients with ART initiation at WHO clinical stage IV had a 2.48-fold higher risk of death than those at stage I (aHR, 2.48; 95% CI, 1.17-5.23).The first year following ART initiation is critical in HIV/AIDS treatment, emphasizing the need for intensified follow-up and monitoring to facilitate successful immune system reconstruction. Older age, male sex, injection drug use, baseline CD4+ T lymphocyte count <200 cells/μL, and WHO clinical stage IV are associated with an increased risk of death. Tailored treatment and management strategies should be implemented for patient populations at higher risk of mortality and with a poorer prognosis.